Bivalent Fears of Evaluation in Social Anxiety: Evaluation of an Extended Psychoevolutionary Model - Glen W. Bates; Pragalathan Apputhurai; Simon R. Knowles (MDPI AG, 2024)
Fears of negative evaluation (FNEs) and fears of positive evaluation (FPEs) comprise a bivalent model of evaluation that can explain the aetiology and maintenance of Social Anxiety Disorder (SAD). In this study, we examined an extended version of this model which incorporates two related cognitive processes (concerns about reprisal and discounting of positive outcomes) as partial mediators of the effects of FNEs and FPEs. We built on earlier work by including a broader measure of social anxiety across different social situations and comparing models for groups of participants with and without probable SAD. Structural equation modelling was utilised to test the model in a sample of 890 university students (74.8% female, mean age 29.49). We replicated the findings of Cook et al. in the overall sample and in the group with probable SAD. FNEs and FPEs predicted social anxiety directly and were serially mediated by concerns about reprisal and discounting positive outcomes. The model was also a good fit for those without SAD; however, in the model, FNEs were no longer a direct predictor of social anxiety. The findings confirm the utility of the extended bivalent model and have implications for psychoevolutionary accounts of social anxiety.